Pengaruh Muscle Fatique Anggota Gerak Bawah Terhadap keseimbangan Statis - Hidayat, Muhammad Wahyu, Yulisna Mutia Sari, SST.FT, M.Sc (GRS), Totok Budi Santoso, SSt.FT, MPH (2017)
ABSTRACT PHYSIOTHERAPY UNDERGRADUATE STUDY PROGRAM HEALTH FACULTY MUHAMMADIYAH UNIVERSITY SURAKARTA THESIS, DESEMBER 2016 41 Pages MUHAMMAD WAHYU HIDAYAT THE EFFECT OF LOWER LIMB MUSCLE FATIGUE ON THE STATIC BALANCE (Supervised by: Yulisna Mutia Sari, SST.FT, M.Sc (GRS)) Background: Fatigue (muscle fatigue) has been considered as an early indication of the adverse effects on postural balance control mechanism. Fatigue affects the capacity of the physical, mental and emotional level of a person, which can result in the lack of alertness which is indicated by the decline reaction to something and reduced the motor skills. Research Objective: To find out the effect of lower limb muscle fatigue on the static balance. Research Method: This research is a quasi-experimental research with pretest and posttest design. The sampling was done by using purposive sampling technique with judgment sampling through the inclusion and exclusion criteria, the number of samples obtained for this research was 14 people. The measurements on the static balance before and after the treatment was done by using the Wingate Cycle Test, meawhile the measurement of the static balance (postural) was performed by using a scale measurement of Rail Balance Test. Results: The results based on the Wilcoxon Signed Rank Test on the pre-test and post-test on the static balance obtained the value of Z -3.145 with a significance pvalue 0,002, therefore, the value is less than the significance level, at 0.05 (0.002 <0.05). Conclusion: There is an effect of lower limb muscle fatigue on the static balance. Keywords: Muscle Fatigue, lower limbs, static balance, Wingate Cycle Test, Balance Rail Test.